Integral equations of scattering in one dimension - Barlette, Vania E.; Leite, Marcelo M.; Adhikari, Sadhan K. [UNESP] (My University, 2001)
A self-contained discussion of integral equations of scattering is presented in the case of centrally symmetric potentials in one dimension, which will facilitate the understanding of more complex scattering integral equations in two and three dimensions. The present discussion illustrates in a simple fashion the concept of partial-wave decomposition, Green's function, Lippmann-Schwinger integral equations of scattering for wave function and transition operator, optical theorem, and unitarity relation. We illustrate the present approach with a Dirac delta potential. © 2001 American Association of Physics Teachers.